The Influence Of Emotional Intelligence And Employee Empowerment On Employee Performance At PT. Bank Muamalat KCP. A Rivai Palembang - Rafiq, M.; Aryanti, Rahmi; Effendi, R.Y; Hermantoalyafiq, Hermantoalyafiq (Journal of Management, Economic, and Accounting, 2025)
This study aims to examine the influence of emotional intelligence and employee empowerment on employee performance at PT Bank Muamalat KCP A. Rivai Palembang. The methodology used in this research is quantitative, with data collected through the distribution of questionnaires to 38 respondents. The data collected were processed using multiple linear regression, t-test, F-test, and classical assumption tests to ensure the validity and reliability of the results. The analysis results reveal that both emotional intelligence and employee empowerment have a significant effect on employee performance, both independently and collectively. Emotional intelligence contributes to how employees manage their emotions and relationships, leading to better decision-making and work performance. Meanwhile, employee empowerment enhances employees' sense of autonomy, responsibility, and engagement, which in turn improves their performance. These findings suggest that improving emotional intelligence and increasing employee empowerment can be effective strategies to enhance employee performance in the organization. The study provides valuable insights for organizational management, especially in the context of PT Bank Muamalat KCP A. Rivai Palembang, to focus on developing these aspects to improve overall performance.